2019
DOI: 10.1101/550756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rare Microbial Taxa Emerge When Communities Collide: Freshwater and Marine Microbiome Responses to Experimental Seawater Intrusion

Abstract: Whole microbial communities regularly merge with one another, often in tandem with their environments, in a process called community coalescence. Such events allow us to address a central question in ecology – what processes shape community assembly. We used a reciprocal transplant and mixing experiment to directly and independently unravel the effects of environmental filtering and biotic interactions on microbiome success when freshwater and marine communities coalesce. The brackish treatment and community m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 67 publications
5
8
0
Order By: Relevance
“…The simplest coalescence outcomes would be one community asymmetrically dominating if a large proportion of its constituent species' populations are better adapted to the abiotic environment, and hence monopolize resources faster than the ecologically equivalent populations within other communities [13,26]. Recent theory has shown that more diverse communities are more likely to asymmetrically dominate because they have a higher chance of containing better adapted populations (selection effects) [42]; a result consistent with previous empirical work [17,43]. However, this simple prediction does not take into account structural differences between communities' species interaction networks.…”
Section: (A) Competitionsupporting
confidence: 73%
See 1 more Smart Citation
“…The simplest coalescence outcomes would be one community asymmetrically dominating if a large proportion of its constituent species' populations are better adapted to the abiotic environment, and hence monopolize resources faster than the ecologically equivalent populations within other communities [13,26]. Recent theory has shown that more diverse communities are more likely to asymmetrically dominate because they have a higher chance of containing better adapted populations (selection effects) [42]; a result consistent with previous empirical work [17,43]. However, this simple prediction does not take into account structural differences between communities' species interaction networks.…”
Section: (A) Competitionsupporting
confidence: 73%
“…First, the 'resident advantage' outlined in §2 as the experimental studies aforementioned in this section coalesced communities into a common garden environment [7,15,54]. When coalescence occurs as invasion, the nonresident community is likely to be less successful as the niches present are occupied and potentially different from that which species are adapted [17,25,26]. Experimentally, local adaptation to the environment gave resident bacterioplankton communities a competitive advantage, and naive communities a disadvantage, in coalescence [55,56].…”
Section: (A) Competitionmentioning
confidence: 98%
“…3), it is unlikely that the increase in observed bacterial richness is due to mixing of species pools via the mixed treatments. Instead it is likely that rare taxa, which we didn't detect at the beginning, become dominant in intermediate salinities (Rocca et al, 2019) and that there was higher immigration from natural sources to freshwater treatments than other treatments. We do, in fact, expect passive dispersal via wind (Nemergut et al, 2013).…”
Section: Discussionmentioning
confidence: 61%
“…Reduction in alpha diversity could be expected to reduce the possibility of asymmetric dispersion of a variety of rare organisms in neighboring habitats (reduction in beta diversity). However, the collision of microbiotas creates new configurations in which rare taxa could emerge (Rocca et al, 2018(Rocca et al, , 2019. The application of zeta diversity metrics (measuring the degree of overlap in the type of taxa present between a set microbiotas) will be most useful to illustrate the spatial structure of multispecies distributions in various environments, and therefore the dimensions of microbiome merging (Hui and McGeoch, 2014).…”
Section: Communication Between Microbiomes Of Different Species Micromentioning
confidence: 99%
“…The dynamics of microbiome merging are insufficiently understood (Roughgarden et al, 2018). New observations, suggesting the modular structure of microbiota (Earle et al, 2015;Tropini et al, 2017), indicate the possibility of a "recombinational merging" within and between microbiomes, eventually resulting in emerging taxa and emerging communities (Rocca et al, 2018(Rocca et al, , 2019. In the soil, specific microbial aggregate communities can be considered "microbial villages, " periodically connected through wetting events, where soil moisture is increased as a result of rainfall infiltration, allowing for the transfer of bacterial organisms and genetic material (Wilpiszeski et al, 2019).…”
Section: Microbiota Community Coalescencementioning
confidence: 99%